Analisis dan Perancangan Sistem Basis Data pada Rumah Sakit - Indrajani, Indrajani (Bina Nusantara University, 2010)
The purpose of this study is to analyze and design a database to support the information needs of hospitals, especially in Customer Relationship Management (CRM). The method used is the method of collecting data by using data searching techniques that include interviews, document study, observation and literature study. Then the research uses the methods of analysis and database design database design that includes conceptual, logical, and physical. The conclusion the database system capable of storing data is integrated, hospital information needs, and improve health services to the customers in this patient in particular and society in general. Conclusions that can be gained from this research is the existence of this database system so the hospital can manage customer data and conducted traksaksi customers, improve the effectiveness in obtaining customer satisfaction and loyalty where customers are able to promote his experience to new customers, and become a hospital options through improved health services to the community.